2020
DOI: 10.56278/tnl.v14i2.1660
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Teacher Education in the Philippines: Observations and Prospects

Abstract: In cognizance of the role of graduate education in human capital development and nation building, the present study aimed to assess the status of graduate teacher education in the Philippines by describing the profile of graduate teacher education programs in both public and private higher education institutions (HEIs). To achieve the purpose of the study, the researchers used a descriptive research design wherein profile data on HEIs’ program offerings, program accreditation levels, and enrolment and graduati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Research skills-in the Philippines, teachers have been instructed to include school-based action research in their performance appraisals and promotion in accordance with a recent mandate from the Department of Education and the Commission of Higher Education [104]. Furthermore, research skills may be beneficial for teachers who are also pursuing graduate degrees [105].…”
Section: Needs Of and Barriers To Tpd (Qualitative Results)mentioning
confidence: 99%
“…Research skills-in the Philippines, teachers have been instructed to include school-based action research in their performance appraisals and promotion in accordance with a recent mandate from the Department of Education and the Commission of Higher Education [104]. Furthermore, research skills may be beneficial for teachers who are also pursuing graduate degrees [105].…”
Section: Needs Of and Barriers To Tpd (Qualitative Results)mentioning
confidence: 99%
“…Several studies have corroborated to this finding. The findings of the study of David (2020) revealed that there is disparity in enrollment numbers between master's and doctoral levels, with fewer students and graduates at the doctoral level.…”
Section: Results and Discussion Problem 1 What Is The Respondents' Ch...mentioning
confidence: 99%
“…Another arising factor is that because the Philippine educational system has seen a significant increase in teachers pursuing higher education after their bachelor's degree (David et al, 2020), it is conceivable that this phenomenon has increased the level of competition among teachers, prompting them to pursue higher education to achieve a higher labor market value. However, apart from the ostensible practical benefits of a doctoral degree, teachers are also driven by personal aspirations and ideals that are influenced by their upbringing and past experiences as students and teachers.…”
Section: Previous Experiences and Factors That Prompted Stem Teachers...mentioning
confidence: 99%